2021
DOI: 10.1186/s12935-021-02099-0
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potentials of resveratrol in combination with radiotherapy and chemotherapy during glioblastoma treatment: a mechanistic review

Abstract: Glioblastoma, WHO grade IV astrocytoma, is the most aggressive type of brain tumors. These cancerous cells have a rapid growth rate, tendency to penetrate vital brain structures, molecular heterogeneity, etc. and this cancer is associated with a poor prognosis and low survival rate. Due to the resistance of glioblastoma cells to conventional therapeutic modalities (such as radiation therapy and chemotherapy) as well as the adverse effects of these modalities, the researchers have attempted to discover an appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 183 publications
(234 reference statements)
0
25
0
Order By: Relevance
“…21,[68][69][70][71] Oxidative stress is commonly recognized as one of the leading causes of chemotherapy-induced cardiotoxicity 20,82 ; as the amount of free radicals increases in this condition. [83][84][85][86] In this regard, doxorubicin can interact with oxygen molecules to form ROS in cardiac cells and subsequently cause elevated levels of oxidative stress. 87 The doxorubicin-generated ROS attack the cell macromolecules, leading to the malfunction of the heart tissue.…”
Section: Discussionmentioning
confidence: 99%
“…21,[68][69][70][71] Oxidative stress is commonly recognized as one of the leading causes of chemotherapy-induced cardiotoxicity 20,82 ; as the amount of free radicals increases in this condition. [83][84][85][86] In this regard, doxorubicin can interact with oxygen molecules to form ROS in cardiac cells and subsequently cause elevated levels of oxidative stress. 87 The doxorubicin-generated ROS attack the cell macromolecules, leading to the malfunction of the heart tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Among the important medicators involved in the apoptosis process are caspase enzymes, Bcl-2, p53, BAX, Bcl-XL, ceramide, PARP, nuclear factor of activated T cells 5 (NFAT5), and so on [ 76 87 ]. One of the characteristics of most cancerous cells is the evasion of apoptosis; as any reduction or irregularity of this pathway invariably accompanies tumorigenesis and maintains malignant progression [ 88 ]. Some chemotherapeutic agents are able to induce apoptosis in tumoral cells [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RES can successfully penetrate the BBB and, therefore, can be employed as an effective therapeutic or protective agent against CNS lesions/disorders and tumors, such as glioblastoma [ 131 ]. Some studies have also shown that RES, as a radio/chemo sensitizing agent, can improve the efficacy of radiotherapy/chemotherapy drugs against glioblastoma cells [ 132 ]. Below we examine in detail what is the chemopreventive and antitumor role of RES in glioblastoma.…”
Section: Natural Compounds In the Therapy Of Gliomamentioning
confidence: 99%